Implementation Of A Simple Linear Regression Method For Webgis Based Prediction Of North Timor Central Timor District Perumda Water Use - Conceicao, Helidora Jelia Sasiana; Rema, Yasinta Oktaviana Legu; Lestari, Anastasia Kadek Dety (Politeknik Negeri Lhokseumawe, 2025)
The increasing need for clean water along with population growth is a challenge for the provision of drinking water services, especially in North Central Timor Regency. The Tirta Cendana Regional Drinking Water Company (PDAM) plays an important role in meeting this need, although water availability is influenced by rainfall and population. The aim of this research is to develop an information system that predicts clean water usage based on the number of customers using a simple linear regression method. The system was designed using the waterfall method and integrated into a WebGIS platform to manage water supply and usage data, and also provides a visualization of water demand in different locations. This research aims to assist PDAM Tirta Cendana in planning water production and improving services to customers, as well as supporting water resource management by local governments to meet community needs in the future.